Could AI Anchors Replace Real Anchors in News Reporting? - Yang, Bowen (Transactions on Computer Science and Intelligent Systems Research, 2025)
In today’s highly developed artificial intelligence technology, AI anchors are widely used in the field of news reporting. With the emergence of zero-error broadcasting by AI anchors, whether the position of real anchors will be shaken by AI anchors, and whether AI anchors can completely replace real anchors in news reporting are the main issues discussed in this paper. Based on CASA paradigm, this paper adopts the experimental method, divides the subjects into AI anchor group and real anchor group, and measures the news memory effect, credibility, favoritism, and immersion of the subjects after watching the video, and finds that the news memory effect, credibility, favoritism, and immersion of AI anchors are lower compared with that of real anchors, and that AI anchors are still unable to completely replace real anchors in news reporting.